ANALISIS PERCEPATAN PROYEK KAPAL KAYU PENCALANG 15 GT MENGGUNAKAN CRASHING PROJECT - Fitri Hardiyanti; Annisa Nanda; Ambikka; Danis Maulana (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
In the utilization of aquatic and fisheries resources, the majority of Indonesian fishermen rely on traditional wooden ship to run their profession. One of the wooden ship project is the "15 GT Pencalang Wooden Ship Project." Which, unfortunately occurs inconsistency between the realization of the work and the initial work planning. Therefore, this research aims to assess the "15 GT Pencalang Wooden Ship Project" by employing the Critical Path method and the Crashing method. This evaluation will help determine the optimal project duration after rescheduling and measure the associated costs. According to the critical path method, there are four specific tasks in this project that can be accelerated i.e. keel / lunas construction, gading work, machinery installation, and finishing. By adding one hour of overtime, the results obtained were successful in reducing the project duration from 139 days to 128 days, while keeping the labor costs at approximately Rp. 290,321,875. In contrast, adding an additional two hours of overtime successfully reduced the project duration from 139 days to 115 days, all while maintaining labor costs at around Rp. 326,553,125. Furthermore, by adding a three-hour overtime shift, the project’s duration was successfully reduced from 139 days down to 111 days, while keeping labor costs consistent at approximately Rp. 356,303,125. As of, the addition of a three-hour overtime shift emerges as the closest alternative to the initially expected project duration in the planning process, which is 102 days equals to 17 weeks.